2020
DOI: 10.5852/ejt.2020.729.1191
|View full text |Cite
|
Sign up to set email alerts
|

A new species of snail-eating snakes of the genus Pareas Wagler, 1830 (Reptilia: Serpentes) from eastern Himalayas, India

Abstract: A new species of snail-eating snakes of the genus Pareas Wagler, 1830 is described from the eastern Himalayas. The species Pareas kaduri sp. nov. differs from all known species of the genus in bearing the following suite of characters: SVL 455–550 mm, TaL/TL 0.184–0.207, brown dorsum with black transverse bands throughout the body, 15 dorsal scale rows throughout the body and mid-dorsal vertebral scale rows enlarged, 8 rows keeled in males, loreal not touching orbit, ventrals 160–183, subcaudals 65–70 in males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 839 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…For comparison, data for other species were taken from related publications (Boulenger 1900(Boulenger , 1905Pope 1935;Zhao et al 1998;Grossmann and Tillack 2003;Guo and Deng 2009;Guo et al 2011;Loredo et al 2013;Vogel 2015;You et al 2015;Hauser 2017;Bhosale et al 2020;Ding et al 2020;Vogel et al 2020;Wang et al 2020). In addition, we examined the topotypic specimens of Pareas niger preserved in KIZ.…”
Section: Dsmentioning
confidence: 99%
“…For comparison, data for other species were taken from related publications (Boulenger 1900(Boulenger , 1905Pope 1935;Zhao et al 1998;Grossmann and Tillack 2003;Guo and Deng 2009;Guo et al 2011;Loredo et al 2013;Vogel 2015;You et al 2015;Hauser 2017;Bhosale et al 2020;Ding et al 2020;Vogel et al 2020;Wang et al 2020). In addition, we examined the topotypic specimens of Pareas niger preserved in KIZ.…”
Section: Dsmentioning
confidence: 99%
“…Several recent taxonomic studies have demonstrated that the species diversity of Pareinae is still underestimated ( e.g ., Vogel, 2015 ; Hauser, 2017 ; Quah et al, 2019 , 2020 ; Quah, Lim & Grismer, 2021 ; Le et al, 2021 ). The high degree of morphological similarity among closely related taxa of Pareinae often makes species delineation in slug snakes quite challenging ( Guo & Deng, 2009 ; Vogel, 2015 ; Yang et al, 2021 ), suggesting that the molecular data represent an effective tool to help untangle taxonomic controversies when morphological analyses yield inconsistent results ( You, Poyarkov & Lin, 2015 ; Loredo et al, 2013 ; Vogel et al, 2020 , 2021 ; Bhosale et al, 2020 ; Wang et al, 2020 ; Ding et al, 2020 ; Liu & Rao, 2021 ; Yang et al, 2021 ). Application of the integrative taxonomic approach combining evidence from morphological and molecular data resulted in the discovery of several previously unnoticed taxa and allowed to revise several species complexes, including the Pareas hamptoni complex ( You, Poyarkov & Lin, 2015 ; Bhosale et al, 2020 ; Ding et al, 2020 ; Liu & Rao, 2021 ; Yang et al, 2021 ), the P. margaritophorus complex ( Vogel et al, 2020 ; Suntrarachun et al, 2020 ), and the P. monticola complex ( Vogel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of herpetological exploration, we surveyed several localities across the Indian state of Arunachal Pradesh (Bhosale et al 2019;Bhosale et al 2020;Mirza et al 2020). During the expedition, we collected specimens of Cyrtodactylus from three localities, which were later identified to belong to a single species based on morphological as well as molecular data.…”
Section: Introductionmentioning
confidence: 99%